Carbamazepine-induced renal toxicity may be associated with oxidative stress and apoptosis in male rat - Erdem Guzel, Elif; Kaya Tektemur, Nalan; Tektemur, Ahmet; Etem Onalan, Ebru (Taylor & Francis Ltd, 2023)
Carbamazepine (CBZ) is the antiepileptic drug used in epilepsy and some psychiatric disorders. Besides its widely used, many adverse effects have been reported including hematotoxicity, hepatotoxicity, endocrine disorders, and testicular damages due to oxidative stress. However, the role of CBZ on renal toxicity is not fully known. In this study, we attempted to explain the connected mechanisms by focusing on the metabolism of CBZ-induced renal toxicity in rats. Twenty male Wistar-Albino rats were randomized into 2 groups (n = 10); control (1 mL/day distilled water, orally) and CBZ (25 mg/kg/day CBZ, orally) groups. After 60 days, TAS (total oxidant status) and TOS (total oxidant status) levels, histopathological features, some genes involved in apoptosis, 8-hydroxy-2-deoxyguanosine (8-OHdG) activity, and apoptotic cells were assessed of kidney tissue. The oxidative stress index (OSI) was measured from TAS and TOS levels. TOS levels and OSI significantly increased, while TAS levels decreased in the CBZ group relative to the control group. Histopathological observations, Caspase-3 (Casp3), Poly [ADP-ribose] polymerase-1 (PARP-1), 8-OHdG immunoreactivities, and apoptotic cells markedly raised in the CBZ group compared with the control group. Also, mRNA expression of Cytochrome c (Cytc) and CASP3 significantly increased in the CBZ group compared to the control group. In conclusion, long-term use of CBZ may promote renal damage in rats by inducing oxidative stress and apoptosis.
Keywords: Carbamazepine; oxidative stress; renal toxicity; apoptosis; 8-hydroxy-2-deoxyguanosine; poly [ADP-ribose] polymerase-1